Ultimate oil sands mine
Much of the bitumen in Alberta is found in shallow oil sands deposits. The oil sands are surface mined and then processed to remove the bitumen. There are three large oil sands mining projects currently producing oil in Alberta. About four tonnes of oil sands must be mined and processed to produce one cubic metre of oil. Roughly 75 percent of the bitumen can be recovered from the sand; the processed sand then has to be returned to the pit and the site reclaimed. Surface mining is performed with electric power shovels. The two largest projects use the world's biggest trucks and shovels. These huge trucks (up to 350 tonnes) haul the mined oil sand to slurry pipelines where it is pumped to extraction plants. The mining process has advanced considerably since the first commercial project was undertaken 35 years ago; it now recovers 85 percent of the oil sands in place in the mined area.